2017
DOI: 10.1097/mco.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of metabolic diseases

Abstract: Purpose of review To discuss recent evidence from observational and intervention studies on the relationship between fruit and vegetable consumption and metabolic disease. Recent findings Observational studies have consistently demonstrated a modest inverse association between the intake of fruit and leafy green vegetables, but not total vegetables, and biomarkers of metabolic disease as well as incident type 2 diabetes mellitus. This is in contrast to limited evidence from recently published randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…On the other hand, fructose has a lower glycemic index than sucrose (or glucose alone), which might lower some of the post-prandial stress responses of the high sugar diet [111]. Furthermore, fructose is present in fresh fruit and therefore would be considered part of a healthy diet; it even seems higher fruit consumption is associated with a reduced risk for type 2 diabetes [112]. It is possible that excess fructose consumption (not from fruit), contributes to negative metabolic effects when it is a component of an overall unhealthy lifestyle, or metabolic dysfunction is already present.…”
Section: Changes In Carbohydrate Intakementioning
confidence: 99%
“…On the other hand, fructose has a lower glycemic index than sucrose (or glucose alone), which might lower some of the post-prandial stress responses of the high sugar diet [111]. Furthermore, fructose is present in fresh fruit and therefore would be considered part of a healthy diet; it even seems higher fruit consumption is associated with a reduced risk for type 2 diabetes [112]. It is possible that excess fructose consumption (not from fruit), contributes to negative metabolic effects when it is a component of an overall unhealthy lifestyle, or metabolic dysfunction is already present.…”
Section: Changes In Carbohydrate Intakementioning
confidence: 99%
“…Epidemiological studies have suggested that diets high in fruits and vegetables help regulate body weight (obesity) and protect against chronic diseases such as cardiovascular disease, cancer, and diabetes [15][16][17]. However, it is difficult to determine the exact role of individual food components in disease prevention.…”
Section: Glucose Homeostasis: Role Of Insulinmentioning
confidence: 99%
“…Epidemiological studies have suggested that diets high in fruits and vegetables help regulate body weight and protect against chronic diseases such as cardiovascular disease, cancer, and diabetes [16,17,18]. However, the role the individual components of these foods play in disease prevention and treatment is difficult to determine.…”
Section: Introductionmentioning
confidence: 99%